Effects of Spiritual Intelligence-Gratitude Training on Spiritual Quotient of Iranian Adolescents - Hosseini, Maryam (2011)
Adolescents are in desperate need of the skills, knowledge, and competencies to moderate the worldliness of the 21st century. The understanding that emanates from wisdom when applied to spirituality is spiritual intelligence. Hence, the main goal of the current study was to determine whether SI-G (Spiritual Intelligence – Gratitude) training results in measurable increases in SQ (spiritual intelligence). The present quasiexperimental study examined the effect of SI-G training on spiritual intelligence among Iranian students (n = 34) from one private, Iranian school in Kuala Lumpur. We evaluated the effects of the SI-G training program on overall SQ and 22 subscales. Spiritual intelligence was measured using an adapted version of the Integrated Spiritual Intelligence Scale (ISIS) (Amram and Dryer, 2007) to assess students’ spiritual intelligence before the training,at the conclusion of the training and three weeks following the training Results of the pre-test showed that most of the students scored low on the overall SQ (M=3.96) while the subscale Gratitude showed the lowest score(M=2.75) among the 22 subscales. At the conclusion of the training, ttests indicated significant improvements in SQ and some subscales of the ISIS,like: Gratitude, Joy, Acceptance, Mindfulness, Optimism, Self acceptance, sacredness and Egolessness. Three weeks after the training, a follow-up test was conducted revealing a drop in scores on some of the subscales. After comparing the results with the pre-test, however, the training program showed significant, positive increases in SQ. The results lend initial support to the assertion that with SI-G training, spiritual intelligence and its subscales can be enhanced, although three weeks may not be sufficient to make the changes sustainable.